Hubungan antara Body Image dan Subjective Well-Being Pada Remaja Putri - Tesi Saktiva Alwis; Jimmy Ellya Kurniawan (Psychopreneur Journal, 2018)
The assessment of body shape or often called the body image is very common among female adolescents. Previous studies showed the body image greatly affected the psychological well-being of adolescents. Young women who considered  themselves people with worse body tended to undergo depression. This perception is likely to inhibit their subjective well-beings. In reality, the body image did not affect subjective well-being of the individual. This research aims to investigate the relations between body image and subjective well-being in adolescent girls. This research is a correlational quantitative study. The subjects consisted of 175 Faculty of Fashion and Design Business of "X" University in Surabaya, aged 18-24 years. The data collection technique was Total Population Study. Having used SPSS, this study found the statistical calculation where ρ = 0.432 and p-value = 0.000 in the body image and subjective well-being satisfaction dimensions. Meanwhile, the body image and subjective well-being subjective dimensions were r = 0.474 and p-value = 0.000.